Update on in-vivo preclinical research models in adrenocortical carcinoma - Kar, Adwitiya (Curr Opin Endocrinol Diabetes Obes, 2020)
PURPOSE OF REVIEW: The aim of this review is to summarize recent advances on development of in vivo preclinical models of adrenocortical carcinoma (ACC). RECENT FINDINGS: Significant progress has been achieved in the underlying molecular mechanisms of adrenocortical tumorigenesis over the last decade, and recent comprehensive profiling analysis of ACC tumors identified several genetic and molecular drivers of this disease. Therapeutic breakthroughs, however, have been limited because of the lack of preclinical models recapitulating the molecular features and heterogeneity of the tumors. Recent publications on genetically engineered mouse models and development of patient-derived ACC xenografts in both nude mice and humanized mice now provide researchers with novel tools to explore therapeutic targets in the context of heterogeneity and tumor microenvironment in human ACC. SUMMARY: We review current in-vivo models of ACC and discuss potential therapeutic opportunities that have emerged from these studies.